Пятеро бесстрашных: рассказы / М. П. Петров - Петров Михаил Петрович (Удмуртия, 1974)
Экземпляры: Селтинская районная библиотека (аб) (20190121) / Инвентарный номер: 13183 / Цена: 0.15 / Авт.знак: П30 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)6